PERAN MEDIA PENDIDIKAN DALAM MENINGKATKAN KEMAMPUAN BAHASA ARAB SISWA MADRASAH - Azhari Azhari (Jurnal Ilmiah Didaktika, 2015)
Instructional media are used to deliver instructional contents. They can be in the forms of book, tape recorder, cassette, video camera, video recorder, film, photo, picture, graphics, television, and computer. They act as learning sources or physical tools that contained instructional materials to stimulate people to learn. The result of the research done in islamic senior high school, MAN Model Banda Aceh showed that the use of audio media could improve students’ achievement and the ability to write arabic language. Using visual media in writing could improve their achievement in writing as it relies on students’ imagination. Furthermore, from audio visual media, students could have new experience and motivate them to study arabic language.